MAKNA DAN IDENTITAS BUDAYA: KOMUNIKASI SIMBOLIK DALAM CORAK TENUN BUTON - Dasmin Dasmin; La Ode Efrianto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Buton weaving is a cultural heritage rich in philosophical and symbolic values. This study aims to examine Buton weaving from the perspective of motif usage as a representation of the identity of the Buton community. The research employs a descriptive qualitative approach, with data collected through in-depth interviews with local weavers and a literature review to explore the extent to which Buton weaving conveys symbolic meanings and cultural identity through its patterns and motifs. The findings reveal that the motifs used in Buton weaving are often inspired by nature, particularly local flora and fauna, reflecting the close relationship between the Buton people and their natural environment. In addition, traditional elements and local cultural symbols are embedded in the designs, representing social values, customs, and beliefs. The use of bright and contrasting colors is a distinctive characteristic that differentiates Buton weaving from textiles of other regions. Furthermore, the intricate and detailed weaving techniques demonstrate the high level of craftsmanship, artistic skill, and cultural knowledge possessed by local weavers.